Demographic Structures of Gelada (Theropithecus gelada) in Guassa Community Protected Area, Ethiopia (Global Journal of Science Frontier Research, 2015)
In geladas, sociality and population structure are unusual because they establish highly differentiated bonds with other group members. Such bonds are particularly pronounced among female geladas, with female philopatry and male dispersal. In the present study, gelada band size and population structures varied between wet and dry seasons. The mean number of females per harem varied from 4.5 to 7.1. In addition, the mean harem, or reproductive female size in all study bands is not statistically significant within season, or between seasons (P > 0.05). The sex ratio did not also show any significant differences between seasons. However, the adult sex ratio and the mean number of reproductive females within the units were statistically significant (t 10= -5.6, P < 0.05). Gelada population growth rate is relatively high (mean = 17.1 % per annum) in Guassa Community Protected Area, and it could be deduced by the differences in number of birth and death at a given period of time within the natural population. Ratio of females per male was relatively lower in the study bands of geladas in present study area, and it doesn't show a true relationship annual growth rate of gelada population. However, the number of births per female/year has brought a significant change on gelada population.
Keywords: band; birth and death rates; gelada; growth rate; population structure; unit